METAPHOR IN THE FILM SETAN JAWA - Fenda, Intan Yulia Febbyu; Handriyotopo, Handriyotopo (Capture : Jurnal Seni Media Rekam, 2021)
The Setan Jawa film depicts the two main characters' fascinating and expressive body language and motions (Setio and Asih). Accordingly, we formulate the research problem of the Setan Jawa film’s metaphor values. This study uses the metaphorical approach to search for the meanings of the film by analyzing the source and target domains. Our findings indicate that Setan Jawa encompasses both the romance source domain and the tragedy target domain. In sum, Setan Jawa is a film about perseverance, courage, intention, self-sacrifice, and ambition.